Rhythmic Gymnaastics: Exploring Its Benefits And Contributions In The World Of Education (A Literature Review) - Napo, Petronela (JUPE : Jurnal Pendidikan Mandala, 2024)
Health can be maintained in a simple way, namely by cultivating exercise. Exercise is a part of sports that can be accessible to all groups and does not require expensive costs. One of the exercises suitable for body fitness is rhythmic gymnastics. The purpose of this research is to describe the benefits of rhythmic gymnastics and its contribution to the world of education. The method used in this research is a qualitative descriptive method by applying literature review. The data in this research consist of books, journals, and theses related to rhythmic gymnastics. Data were obtained through downloading techniques and followed up with reading techniques to find information that answers the problems in this research. Data were analyzed by applying content analysis, focusing on the formulation of problems to find the benefits of rhythmic gymnastics and how its contribution in education. The results achieved from this research are that rhythmic gymnastics has practical benefits such as training muscle strength, improving flexibility, weight loss, increasing concentration, combating depression, improving sleep quality, and maintaining harmonious social relationships. In addition to the perceived benefits, rhythmic gymnastics also has significance in the field of education, contributing in the form of integration into the curriculum and becoming a topic of achievement in physical education and health, providing motor therapy for children, and serving as a competition venue for schools at the local, national, and international levels.